Reorientation of Rural Development as a Base for Improving Land Ownership Distribution at Farmer Level - Jamal, Erizal (Pengembangan Inovasi Pertanian, 2013)
The problem of unbalanced land distribution at farm level in     Indonesia has hampered many efforts to improve rural livelihoods.    Several development programs that have been implemented by     the government have not been fully benefitted by smallholders     due to various reasons, and in many cases this condition even     further widen inequality, because only  landowners who are able     to take advantage the vast range of opportunities created through     the programs. In the future, a reorientation of rural development     is needed with more emphasis on improving farmers? access to     information, capital, technology, and their capacity to take     advantage of opportunities that are locally available. Reorientation     of rural development will be initiated with changes of the     approaches in the planning and implementation of development,     with emphasis on the development of diverse types of businesses,     as well as capacity building of the community to take advantage     of the growing local opportunities. These efforts need to be     supported by the implementation of rural development with an     integrated approach, through a strong cooperation at the district     level under the coordination of District Development Planning     Agency. Rural development planning should be directed to two     main issues. Firstly, open up new business opportunities, especially     those non-based land activities. Secondly, build the community     capacity to capture the existing business opportunities. The     technologies being developed should be neutral with respect to     farmers land ownership, and the technology dissemination is     supposed to be proportional in order to reach all levels of farmers.